Jihad and Genocide - Rubenstein, Richard L. (Rowman & Littlefield Publishers, 2010)
This book examines the relationship between jihad and genocide, past and present. Richard L. Rubenstein takes a close look at the violent interpretations of jihad and how they have played out in the past hundred years, from the Armenian genocide through current threats to Israel. Rubenstein's unflinching study of the potential for fundamentalist jihad to initiate targeted violence raises pressing questions in a time when questions of religious co-existence, particularly in the Middle East, are discussed urgently each day.